The Association of Hispanic Ethnicity with Nonalcoholic Fatty Liver Disease in Polycystic Ovary Syndrome - Sarkar, M (Curr Opin Gynecol Obstet, 2018)
Polycystic Ovary Syndrome (PCOS) affects 10-15% of reproductive age women and is a recognized risk factor for nonalcoholic fatty liver disease (NAFLD). The more severe form of NAFLD, known as nonalcoholic steatohepatitis (NASH), results in liver inflammation with or without fibrosis, and is now a leading cause of cirrhosis. Ethnic differences are apparent in NAFLD, with higher prevalence in Hispanics, although the role of Hispanic ethnicity on risk for NAFLD/NASH in women with PCOS is not known. Objective: The aim of this study was to evaluate ethnic differences in the prevalence and risk of NAFLD/NASH in women with PCOS. Study Design: Among PCOS women followed in a large academic medical center the association of Hispanic ethnicity with elevated biomarkers of NASH, including plasma cytokeratin 18 (CK18) M30 fragments and/or ALT levels (n=303), was assessed. Prevalence of hepatic steatosis by Controlled Attenuation Parameter (CAP) imaging was also evaluated in a subset of PCOS women (n=35). Results: The median cohort age (n=303) was 28 years (IQR 8), and 15.5% (n=47) were Hispanic, the majority of whom reported white race (94%). Most Hispanic women had hepatic steatosis on imaging, which was markedly higher than in non-Hispanics (83% vs 24%, p=0.005). Approximately 17% of PCOS women had elevated ALT or elevated CK18, which was more common in Hispanics than non-Hispanics, at 34% vs 14%, respectively, p=0.002. On univariate analysis, Hispanic ethnicity was associated with two-fold higher odds of NASH (OR 2.0, 95% CI 1.0-3.9, p=0.038), and the association persisted after adjustment for HOMA-IR and waist circumference (AOR 3.1, 95% CI 1.1-8.9, p=0.034). Conclusion: NAFLD/NASH is an important condition to be considered by PCOS providers and Hispanic women with PCOS are a particularly high-risk group that may warrant routine screening.